MiR-26 family and its target genes in tumorigenesis and development. (January 2021) - Li, Chuangang; Li, Yongyi; Lu, Yufeng; Niu, Zhaorui; Zhao, Henan; Peng, Yan; Li, Molin
Highlights: Aberrant expression of miR-26 can be detected in various kinds of malignant tumors. The expression of miR-26 is regulated at four levels: gene amplification or LOH, SNP, transcriptional regulation, estrogen etc. miR-26's validated target genes are involved in metabolism, proliferation, differentiation, apoptosis, invasion and metastasis of tumor cells. miR-26 plays important roles in tumorigenesis and development. Abstract: The microRNA-26 family, including miR-26a, miR-26b, miR-1297 and miR-4465, is a group of broadly conserved small RNAs with identical sequences at the seed region. The expression of miR-26 could be induced by hypoxia via a HIF-dependent mechanism, and up-regulated during multiple cell differentiation. Accumulating studies have demonstrated that miR-26 family members could be detected in many different kinds of tumors, and their validated target genes are involved in cell metabolism, proliferation, differentiation, apoptosis, invasion and metastasis. The expression of miR-26 might be a potentially valuable biomarker and a new target for cancer therapy. In this review, miR-26 family and its target genes in tumorigenesis and development will be summarized as follows.